Strategies of Non-English Study Program Students in Learning Listening Skill - Norleny Habibah; Dina Rafidiyah; Tenny Murtiningsih (UMBanjarmasin, 2022)
This research aims to determine what strategies students use Intensive English Class (IEC) non-English study programs to learn Listening skills. This research was conducted by asking 10 IEC students to take the Test of English as a Foreign Language (TOEFL). Data were collected through observation and interviews with five students with the highest TOEFL scores. Researchers conducted interviews based on six strategies in listening, which were divided into direct strategies (memory, cognitive, compensation) and indirect strategies (metacognitive, affective, and social). The result of this research is that some students use almost the same strategy in listening. Based on the results of the interviews, social strategies are more effective learning strategies used by students. Based on the results of the interviews, four students chose the social strategy, and one chose the memory strategy.